Memories in Motion: Reconstructing Greek Memoryscapes of Ancient Phrygia - Gandini, Alberto (Ancient Near Eastern studies, 2024)
The purpose of this study is to investigate, from a historical perspective, some aspects of the Greek imaginary regarding ancient Phrygia. More specifically, we aim to provide deeper insights as to how Greek- and Latin-speaking authors tried to make sense, in spatial terms, of the Phrygian world they set in mythical, pre-historical times. Addressing issues from the angle of cultural geography, we will attempt to answer questions such as: which places came to be mostly associated with figures and tales relating to the Phrygian past, serving as Phrygian landmarks in the eyes of Greek observers? How did historical events contribute to shaping the Greek geography of the ancient Phrygian world? Finally, is it possible to indirectly recover, through the thick lens of Greek cultural memory, elements of the cultural geography of Iron Age Phrygians?